Langerhans Cell Histiocytosis Manifests with Acute Severe Hypernatremia during Hospitalization - Kullaya Takkavatakarn; Hansamon Poparn; Pisut Katavetin (Case Reports in Nephrology)
Central diabetes insipidus (DI) is characterized by a deficiency in arginine vasopressin (AVP), an antidiuretic hormone leading to excessive free water loss in the urine and hypernatremia. Central DI can be the first presentation of several occult diseases. However, patients with central DI who have functioning thirst mechanisms and access to water may initially exhibit normal sodium levels. We report a 57-year-old woman who was admitted to the hospital due to cholangitis. Her initial serum sodium was normal and she rapidly developed severe hypernatremia after fluid restriction. The results of the laboratory workup indicated DI, which dramatically responded to desmopressin. MRI showed an ill-defined faint hyper signal intensity in T1, T2/FLAIR lesions involving the bilateral hypothalamus. The histopathological findings confirmed the diagnosis of Langerhans cell histiocytosis (LCH) with multiorgan involvement. Serum sodium returned to normal after receiving desmopressin and water replacement therapy.